HUBUNGAN ANTARA KEMANDIRIAN BELAJAR DAN PROKRASTINASI AKADEMIK SISWA KELAS XI SMA SANTO KRISTOFORUS 1 JAKARTA - Gabriela Basilisa; Yoseph Pedhu (Universitas Katolik Indonesia Atma Jaya, 2021)
Self-regulated learning is the ability of individuals to carry out learning activities on their own initiative without help or coercion from others. Academic procrastination is the habit of students to delay in completing study assignments. This study aims to determine the relationship between self-regulated learning and academic procrastination of class XI students of Saint Christopher 1 Senior High School Jakarta. Data were collected using a rating scale instrument. Based on the test results of the instrument, it was found that the self-regulated learning instrument had 50 valid items from 55 items with the instrument reliability of 0.961; while the academic procrastination instrument has 30 valid items from 40 items with an instrument reliability of 0.935. The result of the correlation between the variables of self-regulated learning and academic procrastination was -0.384. These results indicate that there is a significant negative relationship between self-regulated learning and academic procrastination. This means that the higher the self-regulated learning, the lower the academic procrastination. Conversely, the lower the self-regulated learning, the higher the student's academic procrastination.